Toxicidade de nanopartículas de óxido de ferro (Fe3O4) para o cladócero tropical Ceriodaphnia silvestrii - Gebara, Renan Castelhano (2017)
Nanoparticles (NPs) have been produced on a large scale worldwide for various consumer purposes such as the production of cosmetics, sunscreen, biosensors, human prosthetics and cancer therapy. However, due to its large production, NPs can have water bodies as final destination, where current studies addressing these compounds are not sufficient to estimate the threat that these substances could cause to aquatic organisms. Chronic studies with nano-Fe3O4 are scarce and, to the best of our knowledge, inexistent regarding tropical zooplankton species, although chronic studies are of great importance to predict the effects of the substances because they analyses great part of this organisms life cycle. At present study, we investigated nanoparticles of Fe3O4, to the tropical cladoceran Ceriodaphnia silvestrii using acute toxicity tests (0.00; 0.01; 0.10; 1.00; 10.00 and 100.00 mg L-1) during 48h, and chronic toxicity tests (0.00; 3.125; 6.25; 12.50; 25.00 and 50.00 mg L-1) during 14 days. Characterization of NPs in the exposure medium revealed that they experienced agglomeration and aggregation on a micrometer scale. Results showed non-toxicity of nano-Fe3O4 after 48h of acute exposure (EC5048h > 100.00 mg L-1). ). In chronic tests, treatment of 50 mg L-1 caused significant inhibition of growth and reproduction, affecting the maximum length (inhibited 12.71%), accumulated number of eggs (reduction of 51.99%) and neonates (decrease of 61.37%) per female (Dunnett’s test, p < 0.05). We concluded that nano-Fe3O4, in the 14th day, was toxic to C. silvestrii only at the highest concentration tested (50.00 mg L-1) during this chronic exposure.. The use of nano-Fe3O4 in aquatic environments could be considered safe to this species in concentrations up to 25.00 mg L-1, according to the parameters evaluated.